2004
DOI: 10.1038/sj.onc.1208051
|View full text |Cite
|
Sign up to set email alerts
|

FLIP overexpression inhibits death receptor-induced apoptosis in malignant mesothelial cells

Abstract: Tumors have developed several forms of resistance to receptor-induced cell death. Here, we show that malignant mesothelial (MM) cell lines as well as primary MM cells and normal mesothelial (NM) cells express Fas and TNFrelated apoptosis-inducing ligand (TRAIL) receptors DR4 and DR5. We found that, although Fas expression levels are comparable, only MM cells are resistant to cell death. Furthermore, MM cells show resistance to TRAILinduced apoptosis. Caspase-8 (FLICE) is not activated by death receptors trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 38 publications
(31 reference statements)
6
63
0
Order By: Relevance
“…Cellular death receptor-associated apoptotic inhibitors like cellular FLICE-inhibitory protein (cFLIP) inhibit TNF-␣ and Fas ligand-induced apoptosis (24). These cellular IAPs and interleukin-1␤-converting enzyme inhibitor genes are critically regulated by RelB (NF-B) transcription factors (25,26).…”
Section: During Infection Viral Proteins Target Cellular Pathways Thmentioning
confidence: 99%
“…Cellular death receptor-associated apoptotic inhibitors like cellular FLICE-inhibitory protein (cFLIP) inhibit TNF-␣ and Fas ligand-induced apoptosis (24). These cellular IAPs and interleukin-1␤-converting enzyme inhibitor genes are critically regulated by RelB (NF-B) transcription factors (25,26).…”
Section: During Infection Viral Proteins Target Cellular Pathways Thmentioning
confidence: 99%
“…c-FLIP is a competitive inhibitor of caspase-8 for binding to the TRAIL receptor complex and thus, its activity downregulates the downstream TRAIL signaling pathway (4,13,39). In cancer cells, c-FLIP expression levels are higher than in normal tissue and these elevated levels allow the cells to overcome TRAIL-mediated apoptosis (40,41). Furthermore, recent studies, including our previous investigations, have indicated that transfection of small interfering RNA or antisense oligonucleotides against c-FLIP enhanced death receptor-induced apoptosis in various cancer cells (28,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…While c-FLIP L may function as a fine-tuned regulator that manifests dual pro-and anti-apoptotic actions during development and in normal adult tissues, accumulating evidence indicates an anti-apoptotic role for c-FLIP in diverse types of human cancer [11,13,16,18,20,[101][102][103][104]. Notably, recent reports demonstrated that small interfering RNAs (siRNAs) that specifically knocked down the expression of c-FLIP L or c-FLIP S in cancer cell lines of various types augmented TRAIL-and chemotherapy-induced apoptosis [11,17,25,105]. Therefore, the outlook for the therapeutic index of c-FLIPtargeted drugs appears excellent, not only because of the therapeutic efficacy observed in models of c-FLIP targeting in cancer therapy with TRAIL, but also because the current understanding of c-FLIP action in normal tissues supports the notion that c-FLIP-targeted cancer therapy will be well tolerated.…”
Section: C-flip Variants As Targets For Cancer Therapymentioning
confidence: 99%